Acting Regional Heads and the Governance Deficit in Indonesia’s Decentralised Democracy: Participation, Rule of Law, and Transparency in the Transition to the 2024 Simultaneous Regional Elections - Djoni Gunanto (SWATANTRA, 2024)
The appointment of acting regional heads in Indonesia has generated a significant debate on the quality of decentralised democracy and the implementation of good governance at the local level. Although the appointment mechanism was designed as an administrative solution to fill regional leadership vacancies before the 2024 simultaneous regional elections, it also raised normative and institutional concerns regarding public participation, legal certainty, transparency, and democratic legitimacy. This article examines the role of acting regional heads in implementing good governance principles within Indonesia’s decentralised administrative system. Using a qualitative descriptive and normative approach, the study analyses statutory regulations, constitutional considerations, policy documents, and relevant academic literature. The findings indicate that the appointment of acting regional heads reveals a structural tension between administrative continuity and democratic accountability. In particular, three governance dimensions appear most problematic: limited public participation in the appointment process, weak procedural clarity in upholding the rule of law, and insufficient transparency in the selection and performance evaluation of acting regional heads. The article argues that good governance cannot be reduced to bureaucratic continuity; it requires participatory procedures, transparent institutional design, and accountable exercise of temporary authority. The study contributes to debates on local governance by proposing a procedural governance framework for acting regional leadership based on participation, legality, transparency, and public accountability.